Critical assessment of compacted graphite cast iron machinability in the milling process - da Silva L.R.R. (2020)
© 2020 The Society of Manufacturing EngineersContributing to efforts towards world sustainability, compacted graphite cast iron stands out as one of the most promising materials for the new generation of more efficient internal combustion engines. This material has superior mechanical properties, allowing reduction in the component weight. However, this leads to lower machinability when compared to gray cast iron. This paper aims to evaluate the machinability of the compact graphite cast irons with changes in the microstructure (matrix and graphite) in the milling process. As input variables three different versions of the work material (the regular version; with refined graphite; with refined graphite and addition of Mo, two different cutting speeds, feed rates, tool geometries, tool coatings and machining atmospheres. The machinability will be evaluated considering the tool life and wear mechanisms, surface finish and electric current consumption. The results indicate that the most significant variables for the tool life, surface finish and electric current consumption were, respectively, the tool geometry, feed rate and the workpiece material. Thermal cracks were found to be the main damaging mechanism on the flank of the tools.